Ubicación óptima de reconectadores en el alimentador primario “G” de la subestación Cristianía perteneciente a la Empresa Eléctrica Quito - Sisa Sisa, Victor (2023)
Currently, final consumers impose greater requirements on the quality of service, especially in services provided by electricity distributors, this means that technology, more efficient equipment or elements that improve electricity service must be used. More and more protection and switching equipment must be introduced into electrical networks to minimize the number of users without electricity. Fulfilling the objective of guaranteeing the reliability and continuity of the supply of electrical energy to users, this paper analyzes a methodology for the optimal location of recloser equipment in electrical distribution systems. There are several alternative ways to improve the continuity of energy. One of them is the so-called reconnection of electrical service, since it has been observed in several studies that 85 % of the errors in the distribution networks are not permanent, it is that is, after a certain time the error has been omitted, that is, the fault is cleared. For this reason, the problem is minimized with the installation of disconnect/reconnect equipment called reclosers. By quantifying the reliability of electrical distribution systems and their service quality indices, weak points can be determined and, therefore, identify, quantitatively observe the correct recognition place to make the system more reliable and improve these indices.